Uqubat Ta'zir Jarimah Murtad; Konversi Agama untuk Kepentingan Politik - Zulkarnaini; Fan, Aidil; Fakhrurrazi; Sebgag, Saliha (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
Although restrictions on religious freedom are stipulated in the Qanun, However, judging from modern legal science, both state law and international law, there is no formal law that regulates the sanction of converting, namely apostate fingers. Unlike Aceh, as an Islamic sharia region, Aceh has its own qanun where apostates will be subject to sanctions in the form of flogging, fines, imprisonment, and coaching to re-embrace Islam. This regulation is certainly a serious topic both from the perspective of Islamic and national legal authorities, especially how human rights institutions both locally and nationally respond to it. This article is classified as literature research with a qualitative approach. The methodology used is a comparative study of law, especially between conventional law and Aceh Qanun. The results of the study concluded that sociologically, regarding freedom of religion in Aceh Province, it does not conflict with international human rights because the uqubat ta'zir given to perpetrators is approved by all levels of Acehnese society. Precisely if uqubat ta'zir is not given to the perpetrators of apostate jarimah, then the stability of security and religious order in the province is shaken, and minorities, namely people of religions other than Islam, do not feel oppressed by the sociological impact of the law applied by the people of Aceh.